Architectural History and Globalized Knowledge - Chestnova, Elena; Eck, Caroline van; Fraser, Murray; Hildebrand, Sonja; Hvattum, Mari; Leoni, Claudio; Nichols, Kate; Payne, Alina; Ursprung, Philip; Weidmann, Dieter; Wyss, Beat (2021)
Gottfried Semper’s years in exile in London (1850–1855) were a time of highly inspirational experiences. The London of the first World Expo offered the German architect an immense trove of objects for study and an intellectual surrounding that provided seminal impulses for his innovative cultural-history-based theory of architecture. That revolutionary period found not only politics and society in radical upheaval, but also the world of art and science. Internationalization, and indeed globalization, of knowledge was thereby a particularly distinctive phenomenon, the most important place of which was the capital of the British Empire. The present volume, developed from a joint SNF research project through the Institute for the History and Theory of Art and Architecture of the Università della Svizzera italiana and the Institute for the History and Theory of Architecture at ETH Zurich, positions Semper jointly as an observer and actor during this time. It extends beyond a focus on Semper’s individual person to consider his work in designing, teaching and writing architecture based on his historical, architectural and disciplinary surroundings. The international authors are also interested in the continuation of Semper's London concepts in his later works as well as his overall legacy in the history of ideas.